1354 A Rare Case of Gallstone Ileus Due to Cholecystocolonic Fistula. (12th October 2021) - Shaladi, A; Shrestha, A; Basnyat, P
Abstract: Introduction: Gallstone Ileus (GI) is an uncommon but potentially lethal complication of cholelithiasis. 50 to 70% of gallstones obstruct in the ileum, the narrowest point of the intestine. More uncommonly the gallstone can travel into the large bowel via an incompetent ileo-caecal valve and impact in the colon at a recto sigmoid junction. GI involving the sigmoid colon is extremely rare cause of large bowel obstruction. The gallstone often enters the large bowel through a fistula formation between the gallbladder and colon, and impacts at a point of narrowing, causing large bowel obstruction. Case Report: We describe the case of a 72-year-old man who presented with features of bowel obstruction. CT of abdomen pelvis (CTAP) showed a large 5x5cm intraluminal gallstone obstructing at the rectosigmoid area. It showed presence of pneumobilia and incidental finding of abdominal aortic aneurysm (AAA). An emergency laparotomy revealed a cholecystocolonic fistula. The stone was extracted after milking the stone proximally and loop colostomy formed at colotomy site. The patient made an uneventful recovery. Reversal of stoma was postponed pending endovascular repair of enlarging AAA. Discussion: Presenting symptoms of GI are often non-specific, frequently leading to a delay in diagnosis and treatment. Although no fistula was identified in this patient by imaging, the most common cause of GI in most patients is formation of a cholecystoduodenal fistula. Conclusions: Compared with biliary enteric fistulae, the occurrence of cholecystocolonic fistulae is remarkably rare. Temporary colostomies can be considered for treating these cases alongside one-stage operations